Quantitative Assessment of Hydrological Alteration Caused by Irrigation Projects in the Tarim River basin, China - Lianqing Xue (Nature Portfolio, 2017)
Abstract The Tarim River is the longest inland river at an arid area in China. Deterioration in its ecohydrological system has received much attention world widely. This study presents quantitative assessment of hydrological alterations in the hydrological regime of the Tarim River caused by reservoir irrigation and channel irrigation over a period of over a half century. The improved indicators of hydrologic alteration and range of variability approach were applied to the daily flow rates at the two representative hydrological stations. Our study shows that the annual extreme water conditions (1-, 3-, 7-day annual minimum and extreme low timing) have been altered, compared with the pre-impact period. The average flow rate in July, the 30-day annual maximum flow rates, the date for the maximum rate, the rise rate, and the fall rate show a significant decreasing trend. The improved overall degree of hydrological alteration for the two stations are approximately 68.7% and 61.8%, suggesting a high degree of alteration. This study greatly improved our understanding of impacts of irrigations on the ecohydrological characteristics in the Tarim River.